2011 IEEE Symposium on Security and Privacy 2011
DOI: 10.1109/sp.2011.21
|View full text |Cite
|
Sign up to set email alerts
|

Verifiability, Privacy, and Coercion-Resistance: New Insights from a Case Study

Abstract: In this paper, we present new insights into central properties of voting systems, namely verifiability, privacy, and coercion-resistance. We demonstrate that the combination of the two forms of verifiability considered in the literature-individual and universal verifiability-are, unlike commonly believed, insufficient to guarantee overall verifiability. We also demonstrate that the relationship between coercion-resistance and privacy is more subtle than suggested in the literature.Our findings are partly based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(114 citation statements)
references
References 18 publications
1
112
0
1
Order By: Relevance
“…In the only previous works [37,35] where end-to-end verifiability was considered at a "global level" as we do here, it was expressed with respect to a set of "good" runs γ of the e-voting protocol in the sense that a judge could test whether the protocol operated within the set γ. Even though sufficiently expressive, this formulation has the disadvantage that the set γ remains undetermined and thus the level of verifiability that is offered by the definition hinges on the proper definition of γ which may not be simple.…”
Section: Overview Of the Game Gmentioning
confidence: 99%
See 2 more Smart Citations
“…In the only previous works [37,35] where end-to-end verifiability was considered at a "global level" as we do here, it was expressed with respect to a set of "good" runs γ of the e-voting protocol in the sense that a judge could test whether the protocol operated within the set γ. Even though sufficiently expressive, this formulation has the disadvantage that the set γ remains undetermined and thus the level of verifiability that is offered by the definition hinges on the proper definition of γ which may not be simple.…”
Section: Overview Of the Game Gmentioning
confidence: 99%
“…In [37], the same authors showed that individual verifiability and universal verifiability are not sufficient to guarantee the "global" verifiability of an evoting system. A number of other e-voting systems in the cryptographic setting that do not explicitly deal with E2E verifiability include [19,7,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Küsters et al [21] computationally analysed the level of privacy offered by the ThreeBallot voting system and the proposed system by de Marneffe et al [14], and concluded that the latter provides better privacy than the original.…”
Section: Related Workmentioning
confidence: 99%
“…Vote privacy ensures that the voting system should not release any information about your vote other than the information revealed by the final outcome (in an unanimous vote, of course, the outcome would leak your exact vote, independent of the system in use). This notion of privacy has been precisely defined in both symbolic [6], [7] and computational [8], [9] models for reasoning about cryptographic protocols. The second property is end-to-end verifiability which guarantees the integrity of the election and ensures its transparency by providing verifiable evidence of the accuracy of the result.…”
Section: Introductionmentioning
confidence: 99%